An Analysis of the Internationalisation and Entry Modes of MNCs in Emerging Markets – A Case Study of 7-Eleven in Thailand - Pattanapongthorn, Pitchamol (2017)
The main objective of this dissertation is to examine the factors that influence the choice of entry mode for multinational corporations in an emerging market. Therefore, for this study 7-Eleven has been selected as our company case study. Also, Thailand has been chosen as a case study of an emerging market in this research. Theoretically, the author has applied the eclectic paradigm by John Dunning to identify the factors that influence 7-Eleven’s entry mode in Thailand. Therefore, the conceptual framework of this research benefits from the advantages of the eclectic paradigm. These advantages are the location advantages, which are comprised of four factors; namely, market potential, investment risks, competitions and cultural distance. These four factors were found to influence the entry mode choice of the 7-Eleven on its emergence in Thailand.